2003
DOI: 10.1111/j.1654-109x.2003.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of site conditions and seed dispersal on restoration success in alluvial meadows

Abstract: Abstract. We studied the restoration success of flood plain meadows in the northern Upper Rhine valley, where between 1988 and 1992, 35 ha of arable land was converted into grassland and subsequently managed for nature conservation. Remnant populations of typical alluvial meadow species were found in old meadows and along drainage ditches that dissect the whole area. We analysed the site conditions and phytosociological relevés in old and new meadows. Small differences in site parameters between old and new m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(104 citation statements)
references
References 35 publications
(29 reference statements)
4
96
0
3
Order By: Relevance
“…It has been shown that seeds can potentially be dispersed over such distances along river valleys (Andersson and Nilsson 2002;Vogt et al 2006), but the probability of establishment at particular sites is not well known. Studies on recolonisation of floodplain habitats in restoration projects suggest that this probability is rather low even if source populations occur close to the restoration sites (Bischoff 2002;Donath et al 2003).…”
Section: Plant Population Differentiation and Interactions With Herbimentioning
confidence: 97%
“…It has been shown that seeds can potentially be dispersed over such distances along river valleys (Andersson and Nilsson 2002;Vogt et al 2006), but the probability of establishment at particular sites is not well known. Studies on recolonisation of floodplain habitats in restoration projects suggest that this probability is rather low even if source populations occur close to the restoration sites (Bischoff 2002;Donath et al 2003).…”
Section: Plant Population Differentiation and Interactions With Herbimentioning
confidence: 97%
“…All species are common to species-rich flood meadows along the northern Upper Rhine and represent characteristic families of dicotyledons of these as well as similar grassland habitats (cf. Donath et al 2003). Their seed sizes cover about 70% of the total seed size range of species growing in alluvial meadows (Hölzel and Otte 2004b).…”
Section: Experiments 2: Fate Of Buried Seedsmentioning
confidence: 99%
“…1). This is, for example, the case when characteristic species are unable to return due to dispersal limitations (Donath et al 2003;Ozinga et al 2005;Woodcock et al 2010a). Conservation management may thus have contrasting effects on local and regional diversity patterns and may lead to increased biotic differentiation or conversely, amplify biotic homogenization.…”
mentioning
confidence: 99%